Analisis Hukuman Mati dalam Kasus Tindak Pidana Korupsi ditinjau dari Prespektif Hak Asasi Manusia - Erick Suprianto Nahusona; Vincent Anderson Simanjuntak; Gan Godsend (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Thel delath pelnalty has beleln a folrm olf punishmelnt sincel ancielnt timels and has belcolmel an intelnsel colnvelrsatioln amolng elxpelrts belcausel olf thel colntradictolry valuels helld by its suppolrtelrs and olppolnelnts. This study appliels a nolrmativel lelgal relselarch approlach tol asselss thel implelmelntatioln olf thel delath pelnalty in colrruptioln casels frolm thel pelrspelctivel olf human rights proltelctioln. In this study, thel data analysis melthold useld was qualitativel data analysis with a delscriptivel approlach. Thel usel olf thel delath pelnalty as a sanctioln folr colrruptioln is thel molst elxtrelmel folrm olf punishmelnt folr pelrpeltratolrs olf such crimels, belcausel it invollvels taking livels as a relsult olf thelir actiolns. Thel applicatioln olf thel delath pelnalty is colnsidelreld tol viollatel human rights, as stateld in articlels 28A and 28I olf thel 1945 Colnstitutioln, Articlel 4 and Articlel 9 olf Law Nol. 39 olf 1999, and articlel 3 olf thel UDHR. Thel implelmelntatioln olf thel delath pelnalty in colrruptioln casels sparkeld delbatel frolm a human rights pelrspelctivel. Solmel arguel that such melasurels arel colntrary tol human rights, particularly thel right tol lifel.